Topographic Anatomy and Biometrical Observations on the Lungs of Gaddi Sheep - Pathak, Virender (Indian Journal of Veterinary Anatomy, 2020)
The right and left lungs of Gaddi sheep were roughly triangular. Each lung was divided by deepfissures into distinct lobes. The dorsal border of right lung was formed by the cardiac and diaphragmatic lobes, where as dorsal border of left lung was formed by apical and diaphragmatic lobes. The anterior end of the dorsal border of the lungs extended 0.7-11 cm from the cranial of the 1st rib, whereas the posterior-end of the dorsal border was presented under the 9th -10th rib. The ventral border of each lung rested against the sternum. The right lung was larger in size than left and was divided into four lobes i.e. apical lobe, cardiac lobe, intermediate lobe and diaphragmatic lobe, and the left lung into two lobes i.e. apical lobe and diaphragmatic lobe. In Gaddi sheep, the right apical lobe not only occupied the anterior most position in the thoracic cavity but was alsoplaced in front of the heart and occupied the median position. The mean weight of the lung in Gaddi sheep was 923.91±67.00 g. The cardiac lobe extended from 3rd rib to 5th rib in Gaddi sheep. The cardiac notch measured about 5.70±0.27 cm between ventral border of cardiac lobe and costochondral joint and about 4.36 ± 0.54 cm cranio-caudally at mid point of the notch. The intermediate lobe could be located under ventral half of the 4th and 5th rib of right side of the thoracic cavity.